Asean green rated hotels in Malaysia and the materials finishes in interior design / Norul Haidar Zainudin - Zainudin, Norul Haidar (2015)
The practice of green in commercial building types is slow compared to offices and residential. When this study first started, the availability of green hotels rated by Malaysia’s GBIM did not exist as of yet. ASEAN Green Standard, an affiliation of Malaysia’s Ministry Industry was the available alternative; thus is referred to instead. The aim of this study is identifying interior finishes and furnishing whether the materials applied are of green materials. The objectives is observing, recording and analysing the material finishes applied within the lobby, lounge, restaurant and rooms of ASEAN Green Standard rated hotel. Andaman Langkawi and two wings from Shangri-La Rasa Sayang Resort and Spa were the case studies. Questionnaires were given to the hotel’s guests and interviews were conducted to seek experts’ views on the finishes of the ceiling, walls, floors and furniture of the spaces. Limitations of the study were collecting data since privacy and comfort of the guest is prioritized. The findings show that ceilings are mostly of plaster finishes. Walls are mostly are of timber while floors are mostly of carpet. As for furniture, most used finishes is of timber. The finishes in these hotels are mostly of common materials. A better green alternative material could have been used instead. For further research, emphasising on one or two material finishes is advisable for more in-depth understanding. This study ended up being very vast and general where the status of each material finishesis still vague as history of each material is absent.